The relationship between anxiety levels and breast milk production in postpartum mothers - Kasmia, Yuni; Hartati, Dwi; Meihartati, Tuti; Astutik, Widya (Institute of Computer Science (IOCS), 2024)
Exclusive coverage of breast milk (ASI) at RSUD dr. Abdul Rivai Berau in 2021 was 62.44% and in 2022 it decreased to 46.24%, this can be caused by psychological factors experienced by postpartum mothers in the form of anxiety which inhibits the release of breast milk. To determine the relationship between anxiety levels and breast milk production in postpartum mothers at RSUD dr. Abdul Rivai Berau. This type of research is quantitative with analytical survey research and cross sectional design. The population is postpartum mothers with normal delivery at RSUD dr. Abdul Rivai Berau in September 2023 numbered 72 people, based on the Slovin formula with a sample of 42 people. The instruments used in the research were the Taylor Manifest Anxiety Scale anxiety scale questionnaire which was modified from Ameliasari's (2019) research and the breast milk excretion observation sheet. Data analysis used the Chi Square test. The level of anxiety in postpartum mothers at RSUD dr. Abdul Rivai Berau mostly had mild anxiety at 17 respondents (40.5%), while 10 respondents (23.8%) had moderate anxiety. Expression of breast milk in postpartum mothers at RSUD dr. Abdul Rivai Berau mostly had abnormal breast milk production of 22 respondents (52.4%), while 20 respondents (47.6%) had normal breast milk production. There is a relationship between anxiety levels and breast milk production in postpartum mothers at RSUD dr. Abdul Rivai Berau (p value = 0.048 < α: 0.05). There is a relationship between anxiety levels and breast milk production in postpartum mothers.